2020
DOI: 10.1016/j.bbi.2020.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Subjective neurological symptoms frequently occur in patients with SARS-CoV2 infection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
199
1
24

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(231 citation statements)
references
References 41 publications
7
199
1
24
Order By: Relevance
“…Custom screening tools were used by four Chinese studies [70][71][72][73] for evaluating depression, anxiety, and/or sleep disturbances. Two studies 74,75 used interviews for evaluating depression, anxiety, and sleep disturbances. The interview results were reviewed and confirmed by expert neurologists; however, the exact diagnostic criteria and interview questions were not disclosed in these studies.…”
Section: Outcomes and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Custom screening tools were used by four Chinese studies [70][71][72][73] for evaluating depression, anxiety, and/or sleep disturbances. Two studies 74,75 used interviews for evaluating depression, anxiety, and sleep disturbances. The interview results were reviewed and confirmed by expert neurologists; however, the exact diagnostic criteria and interview questions were not disclosed in these studies.…”
Section: Outcomes and Measuresmentioning
confidence: 99%
“…We included 31 studies 43,44,[70][71][72][73][74][75] with 5153 patients in our analysis, including two preprint articles 43,93 (see Fig. 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Manifestations such as insomnia, anxiety, post-traumatic stress symptoms (PTSD), psychosis and mood disorders have been described in several reports (see Table 1; Dinakaran et al, 2020;Liguori et al, 2020;Nalleballe et al, 2020;Rogers et al, 2020;Romero-Sanchez et al, 2020;Vindegaard and Benros, 2020). A study that retrieved data from a global health collaborative platform that included medical records of 40,469 COVID-19 positive cases, mostly from the United States (US) (76%), found that 22.5% had neurological and/or psychiatric manifestations, being anxiety and related disorders the most prevalent (4.6%) (Nalleballe et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 99%
“…An Italian surveybased study observed sleep impairment as the most commonly reported neurological symptom (94/103 patients). 73 A prospective cross-sectional study from the USA showed that impaired sense of smell was associated with anxiety and depressed mood. 74 Finally, a UK-wide surveillance study recorded 23 patients with neuropsychiatric disorders, among them new-onset psychosis (10 patients, 43%), neurocognitive syndrome (6 patients, 26%), and affective disorders (4 patients, 17%).…”
Section: Neurological Complicationsmentioning
confidence: 99%